The Damages Resulting from Electronic Interaction - Mahmoud Shaker, Lect. Dr. Shaker; Mahmoud Shaker, Assist . Lect . Alaa (Basra studies journal, 2024)
This research explores the damages resulting from electronic interactions, with a particular focus on audio, written, and visual electronic conversations between a man and a non-related woman, and the associated consequences. Amid the rapid advancements in digital technology and the significant progress in information technology and internet usage across various fields, several new communication methods have emerged. Over time, these methods have continued to evolve, enabling direct electronic communication between individuals via social media platforms. This is facilitated by programs that connect a user’s device with other devices over the internet, offering multiple services, including written conversations where one person writes to another from their device and receives an immediate response. Additionally, this technology supports audio and visual conversations.